FORMATION OF SOCIO-CULTURAL COMPETENCE WHEN TEACHING ENGLISH LANGUAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article highlights the problem of developing sociocultural competence when teaching English. In this regard, the definitions of the concept of “social competence” of various scientists and methodologists are studied, my point of view on this phenomenon is stated, and the components of sociocultural competence are considered. Research activities, in particular project activities, are considered as one of the methods for effectively developing sociocultural competence in the English language lesson.
Keywords: sociocultural competence; formation; culture; traditions; communication